Gender Diversity and Leadership: Breaking the Stereotype - Jacob, Nina; Ambikasadanam, Santhosh; Pratap Singh, Vivek; Gupta, Ranjika; Nanda, Namrata (International Journal of Psychosocial Rehabilitation, 2019)
Purpose: This research aims to find out the impact of gender diversity at workplace in Indian context. Design/ Methodology/ Approach: The primary data was collected with the help of a structured questionnaire. A sample size of 224 was collected from the respondents of IT, educational and retail sectors and the data was interpreted using TOPSIS analysis. Findings: Women do face certain biasness and challenges in the workplace yet they deliver better in the organisation and interestingly, the outcomes reveal that women have better leadership traits than the male counterparts. Practical Implications: This research gives the clue to the recruiters to explore different ways to reduce discrepancies at work place and evaluating the gender competencies while building teams for accomplishing complex tasks. Originality/ Value: The paper contributes to a new dimension towards gender diversity at workplace by integrating Leadership, Discrepancies and Impact with the empirical analysis for multi criterion decision making using TOPSIS